2013
DOI: 10.1002/hbm.22314
|View full text |Cite
|
Sign up to set email alerts
|

Reversing pathologically increased EEG power by acoustic coordinated reset neuromodulation

Abstract: Acoustic Coordinated Reset (CR) neuromodulation is a patterned stimulation with tones adjusted to the patient's dominant tinnitus frequency, which aims at desynchronizing pathological neuronal synchronization. In a recent proof-of-concept study, CR therapy, delivered 4–6 h/day more than 12 weeks, induced a significant clinical improvement along with a significant long-lasting decrease of pathological oscillatory power in the low frequency as well as γ band and an increase of the α power in a network of tinnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 97 publications
9
83
2
Order By: Relevance
“…This finding corroborates with previous studies that indicate that the amount of gamma band activity is correlated to the subjectively perceived tinnitus loudness (van der Loo et al, 2009;Vanneste et al, 2012) and a decrease in alpha power is associated with an increase in gamma power in tinnitus (Adamchic et al, 2012;Adamchic et al, 2014;Lorenz et al, 2009;Ramirez et al, 2009). To a certain extent this fits with the concept of thalamocortical dysrhythmia (Llinas et al, 2005;Llinas et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…This finding corroborates with previous studies that indicate that the amount of gamma band activity is correlated to the subjectively perceived tinnitus loudness (van der Loo et al, 2009;Vanneste et al, 2012) and a decrease in alpha power is associated with an increase in gamma power in tinnitus (Adamchic et al, 2012;Adamchic et al, 2014;Lorenz et al, 2009;Ramirez et al, 2009). To a certain extent this fits with the concept of thalamocortical dysrhythmia (Llinas et al, 2005;Llinas et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, reduction of oscillatory power in the delta/theta and gamma frequency ranges and increase of the oscillatory power in the alpha band in this area is associated with reduction of tinnitus loudness (Kahlbrock and Weisz, 2008; De Ridder et al, 2011b; Adjamian et al, 2012; Tass et al, 2012; Adamchic et al, 2014). The thalamocortical dysrhythmia model provides an explanation for the emergence and persistence of such a pattern of oscillatory activity as a result of sensory differentiation (Llinas et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This is because neurons have to be active in order to unlearn their pathological synaptic connectivity. In this way sustained long-lasting desynchronization is induced, and, as predicted computationally (Tass and Majtanik, 2006; Hauptmann and Tass, 2007; Tass and Popovych, 2012), therapeutic effects were observed in rat hippocampal slice experiments in the context of epilepsy (Tass et al, 2009) as well as in a clinical proof of concept study in tinnitus patients treated with acoustic CR stimulation (Tass et al, 2012a), where both pathological neuronal synchrony (Adamchic et al, 2013) and pathological effective connectivity (Silchenko et al, 2013) considerably decreased. In addition, in parkinsonian (MPTP) monkeys it was shown that unilateral CR stimulation delivered to the subthalamic nucleus (STN) for only 2 h per day during 5 days leads to significant and sustained therapeutic aftereffects for at least 30 days, while standard 130 Hz DBS has no aftereffects (Tass et al, 2012b).…”
Section: Introductionmentioning
confidence: 83%